PENCEGAHAN DAN PENGOBATAN TERATUR HIPERTENSI MELALUI PEMBENTUKAN TIM GERAK CEPAT NAGARI SADAR HIPERTENSI DI WILAYAH KERJA PUSKESMAS PANINJAUAN KABUPATEN SOLOK - Sri Siswati; Shapira Indra; Siska Ramadhani; Cindy Rahma Putri; Faradilla Aninda Raesa; Miftahul Jannah; Rivanni Aftanisa; Ovaria Suwandi; Nikmah Nur YMS; Susie Adriyani (BULETIN ILMIAH NAGARI MEMBANGUN, 2020)
Hypertension is an increase in a person's blood pressure, with a systolic pressure of more than 120 mmHg and a diastolic of more than 90 mmHg, on repeated examinations. Hypertension is a silent killer, posing a death threat. Hypertension requires regular treatment. Many people are not aware of hypertension, so it is important to check health. Hypertension 78,4 % nor regular treatment in the Panininjau Health Centre area. The purpose of this activity is to prevent risk factors for hypertension and treat patients regularly. To overcome this hypertension disease, a breakthrough is needed in anticipating the risk factors for hypertension and treating it. Counselling about hypertension to cadres and community leaders with the support of the Wali Nagari. The meeting began with the distribution of leaflets, briefing the Head of the Panininjau Community Health Centre and the Walinagari Labuah Panjang, dissemination of hypertension, delivering innovations to overcome hypertension problems in the form of the formation of TGC Hypertension involving the community health centre, community and cadres. This Rapid Action Team was successfully formed and inaugurated by the signing of the TGC Hypertension Decree by the Wali Nagari Labuah Panjang. TGC Hypertension is a tangible manifestation of the commitment of the community, community leaders, nagari guardians and Puskesmas Paninjauan to care for hypertension. Puskesmas Paninjauan conducts TGC Hypertension which becomes a pilot for Hypertension Awareness Nagari in its working area.